Customer Loyalty in Insfluence Photograph Malang: Assessment of Service Quality and Customer Satisfaction - Sri Dwiningsih; M. Mastotok Illah; Sarwo Edi (Innovation Business Management and Accounting Journal, 2023)
The purpose of this study was to determine the role of service quality and customer satisfaction in increasing consumer loyalty in influence photography. The method approach used is quantitative multiple linear regression analysis. The sample used was 100 people who used Insfluence Photography services in the city of Malang. The results of this study indicate that service quality plays an important role in increasing consumer loyalty. Consumer satisfaction also plays an important role in increasing consumer loyalty. An important implication of the results of this research is that efforts can be made to increase consumer loyalty in business in the field of photography services, namely by continuing to provide the best service to consumers and supported by continuing to evaluate consumer satisfaction to see negative aspects that make consumers feel dissatisfied.